The Use Of Content Based Instruction In English Language Teaching - Sitti Nurjannah; Erniati Erniati; Jusmaniar N (STKIP Andi Matappa Pangkep, 2020)
Content-Based Instruction is an approach used in English language teaching. This research aims to investigate the use of CBI in improving the students’ achievement in English Language Teaching at SMK Negeri 2 Makassar. This research used quantitative method which is designed in Quasi Experimental. There were two classes taken as a sample they are control group and experimental group. Both of the group were administered pre-test before implementing CBI in the learning process. after the impelementation of CBI, the posttest was administered to know the students’ achievement in English Language Teaching. From the result of data analysis, it was found that the use of CBI in English Language Teaching is effective in improving the students’ achievement. It is proved by the improvement of the students’ score from the pre-test to the post-test.